Hubungan Antara Locus Of Control Internal Dengan Kematangan Karir Pada Guru - Fajriana, Cholisa (2016)
Abstraction. It is very important for the individual early elections presumably his job really is planned by mature, so that the individual within undergo his/her career, individual have steadinessand has in accordance with hihsinterest as well as his talent. Steadinessundergo a career in accordance with self-knowledge, knowledge of the job, and the ability to plan steps toward careers that are expected to be called by the career maturity. One of the factors that influence on career maturity i.e. internal locus of control. Aim of this research is to know the relationship between the locus of control internal with career maturity, so the authors propose the hypothesis "there is a positive relationship between internal locus of control with the career maturity of the teacher". Subject in this study are teacher of private high school in district Kartasura that amount of 90 teachers. Sampling technique was purposive non random sampling. The measuring instrument that is used to reveal the research variables there are 2 kinds of measuring instrument, namely: (1) scale of internal locus of control, and (2) thecareer maturity scale. Data analysis in this study uses of data analysis technique of the correlation product-moment. Based on analysis results,so obtained a very significant correlation between internal locus of control with career maturity or r amount of 0.567 with p = 0.001, its meaning p < 0.01, the meaning that there is a very significant positive relationship between internal locus of control with the career maturity. Higher the internallocus of control so higher career maturity of teachers, and conversely lower the internal locus of control solower the career maturity of teachers. The mean empirical of the internallocus of control variable amount of 76.31 with a mean hypotheticamount of 70, so the mean empirical >mean hypothetic which means in generallythe private teacher entire Kartasura district have internal locus of control that medium. Further the mean empirical of career maturity variables amount of 83.12 bymean hypotheticamount of 72.5. So the mean empirical >mean hypothetic which means in generallythe subject has career maturity is high. The role of the internallocus of control toward career maturity (SE) amount of32.1% so still there is 67.9% other factors besides internallocus of control yang affect the career maturity.